2015
DOI: 10.3329/bccj.v2i2.24081
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates from Tracheal Aspirates and their Anti-microbial Susceptibility in Mechanically-Ventilated Children with Pneumonia Admitted to an Urban Critical Care Ward

Abstract: Background and Aims: Data on Bacterial isolates from tracheal aspirates in children with severe pneumonia requiring intubation and mechanical ventilation especially in developing countries are very limited. We examined the microbial spectrum of bacteria isolated from tracheal aspirate of those children. The antibiotic susceptibility profiles of those bacteria were also examined.Methods: We evaluated the data of all mechanically ventilated children aged 0-59 months admitted to Intensive Care Unit (ICU) of “Dhak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…05(07.14%) & Staphylococcus aureus 03(04.28%) (Table 3). Similar findings were reported in a study done in Bangladesh by Shahunja et al the most common isolates were Klebsiella 45% followed by Acinetobacter 36% and Pseudomonas 14% 20 . Different studies have been performed to assess the bacterial profile and antibiotic susceptibility pattern in tracheal aspirate samples.…”
Section: Materials and Methodsupporting
confidence: 90%
“…05(07.14%) & Staphylococcus aureus 03(04.28%) (Table 3). Similar findings were reported in a study done in Bangladesh by Shahunja et al the most common isolates were Klebsiella 45% followed by Acinetobacter 36% and Pseudomonas 14% 20 . Different studies have been performed to assess the bacterial profile and antibiotic susceptibility pattern in tracheal aspirate samples.…”
Section: Materials and Methodsupporting
confidence: 90%
“…18 The use of prior antibiotic treatment was recognized as the only risk factor associated with CAP caused by multidrug resistant P. aeruginosa. 20 The resistance level of P. aeruginosa to imipenem is 35.2% but lower in meropenem (5.8%) in this study. Ceftazidime which has a good anti-Pseudomonal activity has a low resistance rate at 5.8% which was much lower compared to the result done in Dongguan, China wherein the resistance of Pseudomonas aeruginosa to ceftazidime was 13.61 and 30.99% in a separate study done in children 1-10 years old with lower respiratory tract infection in Nepal.…”
Section: Discussioncontrasting
confidence: 50%
“…12 In the present study, we identified etiological agent by the conventional culture studies of NPA in 47.3% cases, predominance of gram negatives in this population (figure1). Taneja, et al 13 and Shahunja et al 14 …”
Section: Discussionmentioning
confidence: 99%